Designing Curricula for the New Profile “European Expert in Sustainable Local Development” - Dumitrescu, Andrei; Dijmărescu, Manuela-Roxana; Casorzo, Sylvia; Paciello, Elena (Technium Social Sciences Journal, 2022)
Mankind has reached a point where it can no longer ignore the vital problems of the planet. Personalities with insight and awareness not only draw attention to challenges, but also offer solutions. Globally, these solutions have been combined in the 17 Global Goals of United Nations. Nevertheless, not all practical measures to reach these goals can be identified or effectively implemented by the central governments of the countries. There is also an implicit need for greater involvement by local authorities and communities in identifying and implementing specific measures. Subsequently, the need for a new professional figure has emerged. Partners representing local development, VET training, tourism, and academia from 6 countries has joined in a European project to design the profile and the training course for the European Expert in Sustainable Local Development. The stages of the partnership’s approach were: a) identifying the competencies necessary for this expert up to a certain level; b) the study of similar professional profiles existing in the partnership countries in order to identify the necessary competencies and to avoid proposing a profile that is too similar and, implicitly, inefficient; c) designing the training course for the person who will become an European Expert in Sustainable Local Development.